Blastocystis in animal handlers - Salim, H.R.; Kumar, G.S.; Vellayan, S.; Mak, J.W.; Anuar, A.K.; Init, I.; Vennila, G.D.; Saminathan, R.; Ramakrishnan, K. (1999)
The present study investigated whether people working closely with animals were at higher risk of getting infected with Blastocystis hominis. The prevalence of the parasite was determined in two population groups, i.e., animal handlers and normal healthy individuals who did not work with animals. In all, 105 stool samples were collected from animal handlers from 2 local research institutions, a local zoo, and a local abattoir and 163 stool samples were collected from normal healthy individuals residing in high-rise hats in the city. The in vitro culture method used in the study detected that 41 of 105 animal handlers and 17 of 163 flat-dwellers in the city were positive for Blastocystis. This statistically significant finding (P = 0.0000313) shows that people who work closely with animals do stand at risk of acquiring Blastocystis infection.